2020
DOI: 10.3390/molecules25215191
|View full text |Cite
|
Sign up to set email alerts
|

Carvone Decreases Melanin Content by Inhibiting Melanoma Cell Proliferation via the Cyclic Adenosine Monophosphate (cAMP) Pathway

Abstract: Melanin, which determines the color of the skin and hair, is initially synthesized to protect the skin from ultraviolet light; however, excessive melanin pigmentation caused by abnormal cell proliferation can result in various melanocytic lesions. Cyclic adenosine monophosphate (cAMP) is known to regulate cell cycle progression and consequently to inhibit the division of abnormally proliferating cells. In this work, we aimed to test whether carvone, a scent compound from plants, inhibits proliferation and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Next, changes in filaggrin, hyaluronic acid synthase 2 (HAS-2), keratin 1 (KRT-1), MMP-3, and MMP-9 expression, which are important factors associated with photoaging [ 35 , 36 , 37 ], were analyzed at the gene level. After examining the mRNA expression of filaggrin, HAS-2, KRT-1, MMP-3, and MMP-9 in UVB-irradiated HaCaT cells treated with AYC-CS-E, we found that the mRNA expressions of filaggrin ( Figure 4 a) and HAS-2 ( Figure 4 b) were higher in UVB-irradiated HaCaT cells treated with AYC-CS-E than those in UVB-irradiated HaCaT cells not treated with AYC-CS-E.…”
Section: Resultsmentioning
confidence: 99%
“…Next, changes in filaggrin, hyaluronic acid synthase 2 (HAS-2), keratin 1 (KRT-1), MMP-3, and MMP-9 expression, which are important factors associated with photoaging [ 35 , 36 , 37 ], were analyzed at the gene level. After examining the mRNA expression of filaggrin, HAS-2, KRT-1, MMP-3, and MMP-9 in UVB-irradiated HaCaT cells treated with AYC-CS-E, we found that the mRNA expressions of filaggrin ( Figure 4 a) and HAS-2 ( Figure 4 b) were higher in UVB-irradiated HaCaT cells treated with AYC-CS-E than those in UVB-irradiated HaCaT cells not treated with AYC-CS-E.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the expression of MITF also mediates proliferation and differentiation in melanocytes [ 29 ]. It has been reported that natural compound effectively diminished melanin content in melanocytes through suppression of cell proliferation [ 30 ]. The antiproliferative effect and down-regulated MITF-related proteins of cajanin (50 μM) strongly support the further development of this isoflavonoid as an effective anti-melanogenic compound.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic determination of tyrosinase isolated from cajanin-treated human melanin-producing cells was modified from Lv et al, 2020 [ 30 ]. Human MNT1 cells in 6 well-plates (1 × 10 5 cells/well) were cultured in DMEM containing cajanin (0–50 μM) for 24–72 h. Then, the cells were collected by trypsinization and centrifuged at 5000 rpm for 5 min (4 °C).…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of larvicidal activity of Mentha species EOs and their isolated major components against the West Nile virus mosquito (Cx. pipiens 3rd-4th instar larvae) In another experiment [31], carvone was investigated for its ability to reduce melanin content in melanoma cells as well as for its beneficial effects mediated by the cAMP pathway. This study found that carvone decreases the melanin content and inhibits melanoma cell proliferation in a dose-dependent manner.…”
Section: Antiparasitic Activitymentioning
confidence: 99%